2020
DOI: 10.1177/2158244020902082
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Factors Affecting the Achievement of University Students with Logistic Regression Analysis: School of Physical Education and Sport Example

Abstract: In this study, the factors affecting the success of university students were analyzed by logistic regression analysis. In the study, success variable was defined according to the survey information applied to 360 university students studying in School of Physical Education and Sport in Çukurova University and Kahramanmaraş Sütçü İmam University in Turkey, in 2017–2018 academic year. The relationship between the answers to the Likert-type scale questions affecting success variables and the course success was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…Thus, the dependent variable in this model is the probability of an event with a certain value from the explanatory variable [ 36 ]. Furthermore, if the data does not have a normal distribution or mutual covariance, the binary logistic model can be used instead [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the dependent variable in this model is the probability of an event with a certain value from the explanatory variable [ 36 ]. Furthermore, if the data does not have a normal distribution or mutual covariance, the binary logistic model can be used instead [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…This model is based on the cumulative logistic probability function, and the dependent variable is the probability of an event having a specific value from the explanatory variable [68]. The binary logistic model may also be an alternative when the data do not have a normal distribution and mutual covariance [69].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of the research, it can be suggested that the instructors guide and support the students in order to increase the career values and awareness of the students. In their research, Eratlı Şirin and Şahin [30] stated that the creation of a school environment based on the counseling of instructors in institutions that train physical education teachers is a very important factor in terms of mutual trust, communication and support, which students need, in terms of awareness of students.…”
Section: Discussionmentioning
confidence: 99%